Religious Toleration in the Apophthegmata Patrum - Marinides, Nicholas (Journal of early Christian studies, 2012)
In contrast to a general scholarly portrayal of Christian intolerance in the late antique Roman Empire, many instances of toleration are to be found in the Apophthegmata Patrum. The desert fathers of fourth-century Egypt portrayed in the text emphasized orthodoxy, but also interacted peacefully with people of other beliefs due to their observation of the commandments of love and non-judgment. Their social structure and geographical isolation also mitigated factors that led to religious clashes elsewhere. The compilation of the Apophthegmata collections in sixth-century Palestine enshrined such instances of toleration in the broader Christian ascetical tradition.